Integrated System Responses for Families Impacted by Violence: A Scoping Review Protocol - Gear, Claire; Ting, Chien Ju; Eraki, M; Eppel, E; Koziol-McLain, Jane (BMJ Journals, 2021)
Introduction: The impacts of violence have a significant effect on health and well-being, particularly for women and children. Violence within families is widely recognised as a complex problem constituted by constantly interacting and evolving social, economic, health and cultural elements. Calls for integrated services have arisen from growing understanding about the implications of this complexity, which suggest family violence and solutions to it are generated endogenously from the reflexive nonlinear interactions of system agents. Despite these calls for integration, services designed to support families impacted by violence and the systems that design and fund them are often responsive only to one part of the problem and might not pay attention to agent interactions and their adaptive reflexivity. This paper outlines a scoping protocol to explore how integrated approaches to family violence are conceptualised in current literature, with innovative use of a complexity theory lens. Method: Our scoping review protocol follows the framework outlined by Arksey and O’Malley and refined by Levac. It searches 6 databases, 3 journals and 10 websites using keywords to capture the notion of integration and a complex adaptive system, namely the participant (system agents), concept (system agent interaction) and the context (family violence). Selection criteria require the articles to be written in English, have full-text article available, and were published after 2010. Items selected also need to be evidence based showing interaction between system agents. Applying complexity theory, sensitises us to the reflexive patterns of interaction between system elements and routine ways of interacting. Ethics and dissemination: The nature of this review means that ethics approval is not required. Findings will be disseminated via academic publications, conferences and discussions with policy decision-makers. The findings will be used to develop a plan for stakeholder consultation to share and validate learnings and inform future research.